Understanding the conditions of conservation agriculture adoption in Lango region, Uganda. Issue 10 (25th November 2020) - Kaweesa, Sara Helen; Ndah, Hycenth Tim; Schuler, Johannes; Melcher, Andreas; Loiskandl, Willibald
ABSTRACT: To better understand Conservation Agriculture (CA) adoption in mid-northern Uganda, a successfully tried method, the Q ualitative Expert A ssessment To ol for CA (QAToCA) was used. QAToCA is an expert-based, qualitative, self-assessment guide for determining the relative likelihood of CA adoption within a site-specific context. The results show that CA adoption in the region is highly probable. The two main reasons farmers adopt CA techniques are the dissemination strategy as well as the provided information about CA. The tool also highlighted that the prevailing volatile climate and market conditions are the main constraints to adopting CA at household level.